2021
DOI: 10.1093/neuonc/noab015
|View full text |Cite
|
Sign up to set email alerts
|

Roles for hENT1 and dCK in gemcitabine sensitivity and malignancy of meningioma

Abstract: Background High-grade meningiomas are aggressive tumors with high morbidity and mortality rates that frequently recur even after surgery and adjuvant radiotherapy. However, limited information is currently available on the biology of these tumors and no alternative adjuvant treatment options exist. Although we previously demonstrated that high-grade meningioma cells were highly sensitive to gemcitabine in vitro and in vivo, the underlying molecular mechanisms remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…IOMM-Lee and HKBMM, human malignant meningioma cell lines, were obtained from the American Type Culture Collection (Manassas, VA, USA) and from the Riken BioResource Center (Tsukuba, Japan), respectively. Their characteristics as malignant meningioma cells were confirmed in a previous study [ 8 ]. IOMM-Lee cells were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% fetal bovine serum (FBS).…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…IOMM-Lee and HKBMM, human malignant meningioma cell lines, were obtained from the American Type Culture Collection (Manassas, VA, USA) and from the Riken BioResource Center (Tsukuba, Japan), respectively. Their characteristics as malignant meningioma cells were confirmed in a previous study [ 8 ]. IOMM-Lee cells were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% fetal bovine serum (FBS).…”
Section: Methodssupporting
confidence: 71%
“…We recently reported that gemcitabine, a pyrimidine anti-metabolite chemotherapeutic drug, was very effective for high-grade meningiomas, which highly express hENT1 and dCK, a transporter and rate-limiting kinase for gemcitabine, respectively [ 7 , 8 ]. Accordingly, the guidelines of the European Association of Neuro-Oncology (EANO) listed gemcitabine as one of the candidate drugs for the treatment of meningioma [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Furthermore, we recently demonstrated that high-grade meningiomas expressed high levels of human equilibrative nucleoside transporter 1 (hENT1) and deoxycytidine kinase (dCK), which play critical roles in the cellular uptake and activation of gemcitabine, respectively, and also that high-grade meningioma cells expressing hENT1 and dCK at high levels, including malignant meningioma cells, were sensitive to gemcitabine both in vitro and in vivo. 10 In support of these findings, a recent study reported that gemcitabine administered to a small number of patients with recurrent meningiomas on compassionate grounds achieved excellent outcomes, which underscores its potential as a therapeutic agent for aggressive meningiomas and has also led to the commencement of a clinical trial to evaluate its efficacy for recurrent high-grade meningiomas. 11 In addition to its efficacy as a single agent, gemcitabine has been shown to act as a radiosensitizer in tumor cells both in vitro and in vivo.…”
mentioning
confidence: 79%
“…The intracranial implantation of IOMM-Lee cells was performed as previously described. 10 Briefly, after 5-week-old male BALB/cAjcl- nu/nu mice (CLEA, Japan) had been anesthetized and fixed in a stereotactic frame (Narishige, Tokyo, Japan), a burr hole was made in the parietal bone 2 mm posterior and 2 mm lateral to the bregma. IOMM-Lee cells suspended in PBS (2 × 10 5 in 2 µL) were intracranially implanted through the burr hole 4.0 mm below the skull surface with a 25-µL Hamilton syringe (Hamilton, Reno, NV, USA) that was mounted onto the stereotactic frame.…”
Section: Methodsmentioning
confidence: 99%
“…GEM is a synthetic nucleoside analog that discontinues DNA synthesis. GEM enters cells via equilibrative and concentrative nucleoside transporters (hENTs and hCNTs), while hENT1 plays a key role in GEM uptake [ 5 ]. After entering the cell, GEM is phosphorylated to its main active metabolite 2′,2′-difluorodeoxycytidine triphosphate (dFdCTP) by deoxycytidine kinase; therefore, it competes with deoxycytidine triphosphate and takes action to inhibit DNA polymerase [ 6 ].…”
Section: Introductionmentioning
confidence: 99%